Implications of Pervez Musharraf’s Decentralization of Power Agenda to Transform Bureaucratic System of Pakistan - Shah, Syed Aqeel Abbas; Bakht, Naudir (Annals of Human and Social Sciences, 2025)
focusing on how it affected the country’s bureaucratic and administrative structures. The main charge is that Musharraf’s decentralization initiatives were intended to strengthen governance and redress imbalances between the civilian and military sectors. The research method includes a qualitative research design, which mainly relies on secondary sources with a range of government and academic sources, and entails a detailed examination of legislative amendments, policy changes, and their practical implications. The National Reconstruction Bureau (NRB) and the Provincial Finance Commission (PFC) were two important reforms that attempted to transfer authority and funds from the federal to local governments, nevertheless, bureaucracy and political parties posed strong obstacle to the execution, which reduce the efficacy of these changes. However, low resources, poor administration, and pervasive corruption also hampered its efficacy. The paper demonstrates how that decentralization transformed government while confronting institutional and resource restrictions. It recommends better institutions, political consensus, and long-term finance for efficient local governance.